Stylistic features of professional identity in LinkedIn bios of Indonesian job seekers - Rahmadsyah Rangkuti; Elizabeth Rusida Yosephine Br. Tamba; Dian Marisha Putri; Afrahul Fadhillah Parinduri (JL3T (Journal of Linguistics, Literature and Language Teaching), 2026)
This study investigates stylistic features found in LinkedIn bios written by Indonesian professionals and examines how linguistic choices contribute to professional identity construction. Specifically, the study aims to identify dominant stylistic features appearing in LinkedIn bios and analyze their role in shaping professional identity. This research employed a qualitative descriptive method using a socio-cognitive stylistics approach. The data consisted of 30 LinkedIn bios written in English by Indonesian professionals working in digital marketing and related fields. Data were collected through documentation of publicly accessible LinkedIn profiles and analyzed through data condensation, data display, and conclusion drawing. The findings reveal five dominant stylistic features: lexical choices, syntactic structures, tone and stance markers, discourse organization, and metadiscourse. These features contribute to constructing professional identities that emphasize competence, achievement orientation, creativity, and professional engagement. The study concludes that language in LinkedIn bios functions not only as a communicative tool but also as a strategic resource for constructing professional identity in digital professional environments. Furthermore, the findings demonstrate that professionals deliberately use language to highlight their expertise, achievements, and personal values while maintaining a professional image. Through these stylistic choices, LinkedIn bios serve as an important medium for self-presentation, networking, and career development within increasingly competitive digital professional communities.